Construct-it: A board game to enhance built environment students' understanding of the property life cycle. Issue 3 (June 2019) - Hayhow, S.; Parn, E.A.; Edwards, D.J.; Hosseini, M. Reza; Aigbavboa, C.
This article investigates the development of a board game entitled 'Construct-it' as an innovative pedagogical approach (as proof of concept) to augmenting the applied knowledge and understanding of built environment students studying property life cycle analysis. A largely qualitative and inductive methodological approach is conducted to identify and investigate the various pertinent theoretical frameworks that could be adopted; conduct a critical synthesis of extant literature; and develop Construct-it, a game intuitively grounded in practice-based knowledge. The study reveals that games provide a fun, engaging and challenging means of educating students at higher education institutions. It also notes a significant dearth of literature in terms of applying games to students enrolled on built environment programmes. Construct-it can enhance the student's learning experience and knowledge of pertinent industry practice and standards and can complement traditional classroom teaching approaches. The study concludes with directions for the future work required to enhance the development of the novel pedagogical proof of concept presented. Such work will require robust testing and validation of the game to measure its impact on the student learning experience.